2012
DOI: 10.1016/j.it.2011.11.002
|View full text |Cite
|
Sign up to set email alerts
|

How Samhd1 changes our view of viral restriction

Abstract: Recent studies have uncovered sterile alpha motif and HD domain 1 (SAMHD1) as the restriction factor that blocks HIV-1 replication in myeloid cells. In contrast to previously identified HIV-1 restriction factors, SAMHD1 does not meet a countermeasure developed by HIV-1. However, HIV-2 and certain simian immunodeficiency virus (SIV) strains express the auxiliary protein Vpx that potently blocks SAMHD1. It is therefore perplexing why this function has been lost or not acquired during the course of lentiviral evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 87 publications
1
42
0
1
Order By: Relevance
“…Germ-line mutations in SAMHD1 have been associated with Aicardi-Goutieres syndrome, a congenital autoimmune disease (23), and more recently SAMHD1 was shown to be an HIV-1 restriction factor operating in nondividing blood cells (24,25). Initially, the restriction function of SAMHD1 was attributed to its dNTPase activity, which was presumed to decrease the intracellular dNTP concentrations to levels incompatible with viral replication (26). Later, it was suggested that restriction of HIV-1 was primarily caused by the nuclease activity of SAMHD1 degrading viral RNA (27).…”
mentioning
confidence: 99%
“…Germ-line mutations in SAMHD1 have been associated with Aicardi-Goutieres syndrome, a congenital autoimmune disease (23), and more recently SAMHD1 was shown to be an HIV-1 restriction factor operating in nondividing blood cells (24,25). Initially, the restriction function of SAMHD1 was attributed to its dNTPase activity, which was presumed to decrease the intracellular dNTP concentrations to levels incompatible with viral replication (26). Later, it was suggested that restriction of HIV-1 was primarily caused by the nuclease activity of SAMHD1 degrading viral RNA (27).…”
mentioning
confidence: 99%
“…15,16 It is expressed widely across most tissue types including in the hemopoietic system and normal B cells. 17,18 In the case of HIV, SAMHD1 is responsible for maintaining the cellular dNTP pool at a level that is inadequate for replication of HIV-1 and other viruses, [19][20][21] thereby preventing viral propagation.…”
Section: Introductionmentioning
confidence: 99%
“…The SAMHD1 enzyme restricts retrovirus infection in macrophages, dendritic cells, and resting CD4 ϩ T cells (28)(29)(30). It was identified through biochemical purification of the accessory factor Vpx encoded by certain lentiviruses (8,9).…”
mentioning
confidence: 99%